ON THE IMPLICATIONS OF A 17 KEV NEUTRINO - Hime, A; Phillips, R; Ross, G; Sarkar, S (1991)
We discuss the implications of the recent measurement of a 17 keV mass component in the electron neutrino sector. Such a heavy state must decay in order to be compatible with cosmology; this requires states additional to those of the standard model. The most likely candidates are either majorons, allowing the decay into massless weakly interacting scalars, or singlet neutrinos, allowing the decay via the Z into light neutrinos. We show that in the latter case there is a lower bound on the lifetime in conflict with the cosmological constraints on this decay channel and on the photon plus neutrino decay channel which is also present. The extensions of the standard model needed to reduce the lifetime are considered. We analyze the mass matrix, playing particular regard to the singlet neutrino case, and discuss how it might be extended to explain the solar neutrino deficit.